Diversity of Hepatitis C Virus Quasispecies Evaluated by Denaturing Gradient Gel Electrophoresis - Harris, K. A. (American Society for Microbiology, 2001)
Denaturing gradient gel electrophoresis (DGGE) was used to study the diversity of hepatitis C virus (HCV) quasispecies. Optimized DGGE running conditions were applied to screen for variations in sequences cloned from amplicons originating from the nonstructural 5b (NS5b) gene of HCV in blood of hemophilia patients, intravenous drug users, and blood donors (five specimens from each study group, ca. 40 clones studied per specimen). Clones identified by DGGE as unique were sequenced. NS5b sequence entropy and mean genetic distance in hemophiliacs did not differ significantly from those in the other groups, pointing to a lack of correlation between HCV diversity and the multiplicity of past HCV exposures. DGGE was also applied to investigate variation in the HCV envelope 2/hypervariable region 1 (E2/HVR-1) in serum samples serially taken from two patients during the seroconversion phase of HCV infection. E2/HVR-1 sequence entropy changes were small and not correlated with rising anti-HCV antibody levels, reflecting mutational changes not mediated by antibody selection.